(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3hgh GdYde, bhdg jdRhegG Cj jdRe GdEWGYI HPdc GdfMh bhdg deG YQaJ ef YOe LQjGf bGYOI GdedGReI aj GdehQO, bhdg Zdi Ydi fMh GdMcheI dCf GdYbd HYOgGs
(3BNQgG (B:s
(3BNQgG(B: (3aEf GdGQGOI Jchf hGYjI dCJjGf GdaYd aj faSg dG EJjGfg ef LgI Cfg eQGO Hd dG jdJa aj MGd GJjGfg Edi GdEQGOI aVdG Yf Cfg eQGOs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs